Pemanfaatan Lahan Bekas Tambang Kapur sebagai Lahan Alternatif Penghasil Hijauan Pakan untuk Ternak Ruminansia - Hadi Prayitno, Caribu; Setiadi, Deni (Seminar Nasional Lahan Suboptimal, 2024)
Prayitno, C. H., & Setiadi, D. (2024). The utilization of limestone post-mine land as an alternative forages producing land for ruminants. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang  21 Oktober 2024. (pp. 11–19).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Post-limestone mining land is widespread throughout Indonesia and causes negative impact in the form of abandoned open lands. The availability of land for forage is very limited, so it is necessary to use the abandoned land such as post-limestone mining land as an alternative forage producing land. Utilizing post-limestone mining land as a producer of forage also contributes to reduce ecosystem damages. Low soil fertility and the type of forages to be cultivated are challenges in making post-limestone mining land as an alternative forage producing land. The innovations to utilize post-limestone mining land are improving the quality and fertility of the soil with organic matter, revegetating legume plants as pioneer plants, and planting cultivated grass and sweet potatoes as an effort to fulfill the forages for ruminant animals.